Propagação Vegetativa da Preciosa (Aniba canelilla (H. B.K) Mez) pelo Método da Estaquia - Siqueira , Jhassem Antônio Silva de (2005)
The precious wood (Aniba canelilla (H.B.K.) Mez) is a native species from Amazon Region. It is a popular species well know in the region for its aromatic tea that can be obtained from their leaves, bark and trunk. It is a species with a great economical potential, because it can give a wood of high quality, it has also medicinal purpose, and nowadays it is being used by the cosmetic industry. The essential oil has a high concentration of nitrofeniletano (a natural odour). This work had the aim to establish a methodology for the propagation by rooting of precious wood species cuttings. Furthermore it aims to evaluate the action of different concentrations of indolbutyric acid (IBA), at 0; 300; 600; 1200; 2000, on t he development of the cutting that were obtained from juvenile and adult material. The experiment was developed in greenhouse with an intermittent mist system during a period of 180 days (around six months). The experiment was statically analysed by completely randomized method, the data were also submitted to analysis of variance and the means were compared by Tukey test analysis at 5% probability. The results indicated that it is possible to promote the vegetative propagation of precious wood by the cutting method, independent of the hormones concentration used at the experiment. The AIB use on the concentration of 2000 ppm favored the rooting (79,04%), the survival (89,43%) and sprouted (64%) of the cuttings coming from juvenile material after 180 days of the implementation of the experiment. The comparison of the means of fresh material weights of aerial part and root, and the weight of the dry material of the aerial part of the plant and also of the cuttings. They did not showed a significative difference among them. . Cuttings from adult material in the treatments here evaluated showed rooting below 1%, and a final survival means of 0,76.